A new species of Cyrtodactylus from the Nicobar Islands, India - Das, I. (The Society for the Study of Amphibians and Reptiles, 1997)
A new species of bent-toed gecko, Cyrtodactylus adleri, is described, based on seven examples from the island of Great Nicobar, India. Although reported as conspecific with C. rubidus, it can be differentiated from the Andamanese species in possessing dark spots (vs. dark bands) on the dorsum; 48-50 imbricate (vs. 38-42 juxtaposed) midventrals; six (vs. four) postnasals; two (vs. three) postcloacal tubercles; and presence of a preanal groove. In the lack of a preanal groove, imbricate ventrals, and dark spots on dorsum, the new species appears close to the poorly known Sumatran endemic, C. lateralis, from which is may be differentiated in its small body size (SVL 53.5-64.7 mm in four adult females, 61.8-68.5 mm in three adult males), dark spots on dorsum, and 48-50 midventrals.